2016
DOI: 10.1007/s00264-016-3133-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local anaesthetic wound infiltration on acute pain and bleeding after primary total hip arthroplasty: the EDIPO randomised controlled study

Abstract: Operative wound infiltration of LIA reduced acute pain after primary THA but did not improve recovery or influence per- and postoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 25 publications
1
49
0
1
Order By: Relevance
“…One patient in the PDI group had a deep vein thrombosis postoperatively. Four studies [10,12,13,16] had not found the complications of infection, wound complication, and nausea, and just reported that there was no significant difference between the 2 groups about the complications. One study [10] also reported the loss of blood between the 2 groups, but no obvious difference was found.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One patient in the PDI group had a deep vein thrombosis postoperatively. Four studies [10,12,13,16] had not found the complications of infection, wound complication, and nausea, and just reported that there was no significant difference between the 2 groups about the complications. One study [10] also reported the loss of blood between the 2 groups, but no obvious difference was found.…”
Section: Resultsmentioning
confidence: 99%
“…Murphy et al [8] reported less morphine use for patients with THA who received local infiltration of an anesthetic (bupivacaine), saline. In the most recent randomized, double-blind study, Villatte et al [10] found the local infiltration technique provided effective pain relief for patients who received postoperative periarticular infiltration of THA with a local anesthetic (ropivacaine), adrenaline, but no effect on recovery and blood loss after surgery. Whereas Busch et al [9] found that patients who had THA would need less postoperative analgesic requirements and also feel less pain when they tried to move their legs if they got the periarticular infiltration of an anesthetic including morphine, and ropivacaine, ketorolac, epinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations